2015
DOI: 10.1007/s00726-015-2000-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of homoarginine and methylarginines with liver dysfunction and mortality in chronic liver disease

Abstract: Previous studies on arginine metabolites reported an association of asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA) with liver dysfunction and an inverse relation of homoarginine (hArg) with cardiovascular risk. The aim of the present study was to investigate the relationships between hArg, ADMA, SDMA, and the dimethylarginine score (DAS, i.e., ADMA + SDMA) and liver dysfunction and survival in chronic liver disease. In 94 consecutive cirrhotic patients admitted to our outpatient liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
(93 reference statements)
0
19
0
Order By: Relevance
“…Recent clinical investigations on these Arg metabolites in adults extend their key importance to other diseases in adults, including multiple sclerosis, chronic liver and kidney disease, obesity, rheumatoid arthritis, coronary artery disease, and peripheral arterial occlusive disease (Dimitroulas et al 2015;Frenay et al 2015a, b;Haghikia et al 2015;Kayacelebi et al 2015c;Kruszelnicka et al 2015;May et al 2015;Pilz et al 2015a;Schneider et al 2015;Sitar et al 2015). In childhood and adolescence, the significance of ADMA or hArg as cardiovascular risk factors is little investigated and incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical investigations on these Arg metabolites in adults extend their key importance to other diseases in adults, including multiple sclerosis, chronic liver and kidney disease, obesity, rheumatoid arthritis, coronary artery disease, and peripheral arterial occlusive disease (Dimitroulas et al 2015;Frenay et al 2015a, b;Haghikia et al 2015;Kayacelebi et al 2015c;Kruszelnicka et al 2015;May et al 2015;Pilz et al 2015a;Schneider et al 2015;Sitar et al 2015). In childhood and adolescence, the significance of ADMA or hArg as cardiovascular risk factors is little investigated and incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 34 studies reporting a total of 39137 participants were included in the final analysis (Table 1)791113141516171819202122232425262728293031323334353637383940414243. Eleven studies were based on 9319 participants with pre-existing renal diseases including 2533 renal transplant recipients715192122252628383943.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies reported that ADMA was significantly associated with all-cause mortality111618, other studies did not find that ADMA was associated with all-cause mortality323342. The different results might be because of the limited number of participants involved in each single-center study in addition to the complicated role of ADMA in vivo .…”
Section: Discussionmentioning
confidence: 96%
“…Mortality rate was found correlated with ADMA, SDMA, and DAS values over median values and homoarginine levels below median value. It was stated that ADMA is one of the indicators of hepatic dysfunction and that ADMA is one of the responsible factors for poor outcome in the patients with cirrhosis (Pilz et al, 2015). In a study conducted in an intensive care unit, baseline ADMA levels of the patients with liver failure that developed due to high-dose administration of acetaminophen at admission to the intensive care unit were found higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The ADMA/DDAH/NO pathway is also one of the affected pathways (Mookerjee et al, 2007a). Increased levels of ADMA observed in hepatic dysfunctions are due to increased levels of protein breakdown or decreased DDAH activity (Mookerjee et al, 2007b;Pilz et al, 2015). The reduction in DDAH activity may originate from local inflammation, from increased oxidative stress, or directly from the reduction in the amount of DDAH protein (Nijveldt et al, 2003b).…”
Section: Discussionmentioning
confidence: 99%